2020
DOI: 10.1002/cssc.202000490
|View full text |Cite
|
Sign up to set email alerts
|

Production of Antiviral Substance from Sugarcane Bagasse by Chemical Alteration of its Native Lignin Structure through Microwave Solvolysis

Abstract: The production of bioactive agents from lignocelluloses has received limited attention because plant cell walls are essentially non‐bioactive. In this study, a chemical reaction is reported, which produces a lignin‐derived antiviral substance from sugarcane bagasse by microwave heating at 200 °C in aqueous glycerol containing 0.5 % H2SO4. The purified fraction, designated as FR200, strongly inhibited the replication of encephalomyocarditis virus (EMCV) in L929 cells without cytotoxicity. HSQC NMR spectra demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…We found that MWL exhibited no antiviral activity, indicating that the antiviral activity is not due to native lignin structures. In our recent study, we found that antiviral activity emerged through severe alteration of the native lignin structure by microwave acidic glycerolysis of sugarcane bagasse. In B1-M2, B1-M3, and B1-M4, the structural alteration of the lignin moiety by acidolysis may affect the antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that MWL exhibited no antiviral activity, indicating that the antiviral activity is not due to native lignin structures. In our recent study, we found that antiviral activity emerged through severe alteration of the native lignin structure by microwave acidic glycerolysis of sugarcane bagasse. In B1-M2, B1-M3, and B1-M4, the structural alteration of the lignin moiety by acidolysis may affect the antiviral activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lignocellulosic biomass, a sustainable bio-resource composed of cellulose, hemicelluloses, and lignin, is a product of photosynthesis. Lignin and carbohydrates are covalently linked to form a lignin–carbohydrate complex (LCC) in the plant cell walls. Over the past decades, extensive studies have been conducted to apply the lignocellulosic biomass in various fields; however, the research into antiviral activity of lignin and lignin-containing substances remains limited. Several research studies reported the antiviral activity of fractions extracted from various media, such as the culture medium of Lentinus edodes, pine cones, Prunella vulgaris, and so forth. However, they suggested that the active components in the studied fractions were lignin or lignin-containing substances.…”
Section: Introductionmentioning
confidence: 99%
“…Ponadto, ligninocelulozy mogą blokować replikację pikornawirusa zapalenia mózgu i mięśnia sercowego (EMCV, ang. Encephalomyocarditis virus) [162] Nanoligniny są produktami powstałymi poprzez transformację polimerów do formy koloidalnych cząsteczek ligniny. Wykazano, że w wodzie związki te powodują agregację i łatwe usuwanie cząstek wirusa CCMV (ang.…”
Section: Ligninyunclassified
“…Lignin structure determines its functions as well as biological activities. [40] Wang et al applied organosolv sequential dissolution to fractionate lignin extracted with ethanol from corn stover. [41] As shown in Table 4, the heterogeneous parent lignin (M w = 8317 g mol À 1 , PDI = 1.82) was fractionated into four relatively homogeneous parts with gradually increasing molecular weight and decreasing phenolic OH content.…”
Section: Lignin Fractionation To Screen Lignin With Specific Biologicmentioning
confidence: 99%